2009
DOI: 10.1007/s10534-009-9241-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic effects of vanadium(III, IV, V)–chlorodipicolinate complexes in streptozotocin-induced diabetic rats

Abstract: Vanadium(III, IV, V)-chlorodipicolinate (dipic-Cl) complexes, including H[VIII(dipic-Cl)2] · 5H2O (V3dipic-Cl), VIVO(dipic-Cl)(H2O)2 (V4dipic-Cl) and K[VVO2(dipic-Cl)] (V5dipic-Cl), were prepared with the indicated oxidation states. Our aim was to evaluate the anti-diabetic effects of V3dipic-Cl, V4dipic-Cl and V5dipic-Cl in streptozotocin-induced diabetic rats. Vanadium complexes were orally administered to diabetic rats at concentrations of 0.1-0.3 mg/ml in the drinking water. We found that vanadium-chlorodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
61
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 40 publications
6
61
0
Order By: Relevance
“…In particular, their potential insulin mimetic capacity has been extensively investigated [10][11][12][13][14][15][16]. It has been shown that VCs can be used to mitigate insufficient insulin response in DM thus presenting insulin-mimetic properties in vitro and [17][18][19][20] in vivo [21][22][23][24], and two of them were tested in clinical trials [25]. To date, the main limitation for the clinical use of VCs in the treatment of diabetes has been their potential toxicity [26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, their potential insulin mimetic capacity has been extensively investigated [10][11][12][13][14][15][16]. It has been shown that VCs can be used to mitigate insufficient insulin response in DM thus presenting insulin-mimetic properties in vitro and [17][18][19][20] in vivo [21][22][23][24], and two of them were tested in clinical trials [25]. To date, the main limitation for the clinical use of VCs in the treatment of diabetes has been their potential toxicity [26].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of vanadium (IV and V) complexes have been synthesized, structurally characterized [28][29][30][31] and their biological activity tested using adequate cellular models by measuring glucose uptake levels [32,33], inhibition of free fatty acid release [33,34] and in vivo studies with diabetic rat models to test their capacity to reverse diabetic features [23,24,35,36]. Among the many vanadium compounds reported in the literature, emphasis is given to the bis(matolato)oxidovanadium(IV) (BMOV) [11,14,37] and the similar one bis(ethylmaltolato) oxidovanadium(IV) (BEOV) [25], the only vanadium compounds tested in clinical trials to date, but other compounds like bis(1,2-dimethyl-3-hydroxy-4-pyridinonato)oxidovanadium(IV), [VO(dmpp) 2 ] [31,33,[36][37][38][39][40][41], bis(picolinato)oxidovanadium(IV) [VO(pic) 2 ] [24,42,43] and bis(allixinato)oxidovanadium(IV) [18,44,45] have also attracted much interest due to the positive results which have been obtained through in vitro and in vivo studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the moment several vanadium compounds (VCs) such as bis(maltolato) oxovanadium(IV) (BMOV) and bis(ethylmaltolato) oxovanadium(IV) (BEOV) [5][6][7], (dipicolinato)oxovanadium(IV) [8,9], bis(picolinato)oxovanadium(IV) [10], bis(allixinato) oxovanadium(IV) [11][12][13], and bis(1,2-dimethyl-3-hydroxy-4-pyridinonato) oxovanadium(IV) (VO(dmpp) 2 ) [14][15][16] have shown a promising antidiabetic activity. Actually, BEOV passed phases I and II in human trials [6].…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation state of the VC seems to be also an important feature for its therapeutic effectiveness and research has been carried out in this field [12]. However, an accurate ex vivo/in vivo determination of the oxidation state of the V species which actually are responsible for the antidiabetic properties remains unclarified.…”
Section: Introductionmentioning
confidence: 99%